Characteristics and outcomes of thymomas in Latin America: results from over 10 years of experience (CLICaP-LATimus) (2021)
Background: Thymomas are a group of rare neoplasms of the anterior mediastinum.The objective of this study was to describe the demographics, clinical characteristicsand treatment approaches in Latin America.Methods: This was a retrospective multicenter cohort study including patients withhistologically proven thymomas diagnosed between 1997 and 2018. Demographics, linicopathological characteristics and therapeutic outcomes were collected locallyand analyzed in a centralized manner.Results: A total of 135 patients were included. Median age at diagnos is was 53 yearsold (19–84), 53.3% (n = 72) of patients were female and 87.4% had an ECOG perfor-mance score ranging from 0–1. A total of 47 patients (34.8%) had metastatic diseaseat diagnosis. Concurrent myasthenia gravis occurred in 21.5% of patients. Surgerywas performed in 74 patients (54.8%), comprising 27 (20%) tumorectomies and47 (34.8%) thymectomies. According to the Masaoka-Koga system, overall survival(OS) at five-years was 73.4%, 63.8% and 51%, at stages I–II, III–IVA and IVB,respectively (p = 0.005). Furthermore, patients with low lactate dehydrogenase(LDH) (≤373 IU/L) at baseline and myasthenia gravis concur rence showed signifi-cantly better OS (p = 0.001 and p = 0.008, respectively). In multivariate analysis, highLDH levels (HR 2.8 [95% confidence interval [CI]: 1.1–7.8]; p = 0.036) at baselineand not performing a surgical resection (HR 4.1 [95% CI: 1.3–12.7]; p = 0.016) weresignificantly associated with increased risk of death.Conclusions: Our data provides the largest insight into the clinical characteristics andoutcomes of patients with thymomas in Latin America. Survival in patients withthymomas continues to be very favorable, especially when subjected to adequatelocal control.